2019
DOI: 10.1167/iovs.19-27145
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Alpha and Intrinsically Photosensitive Retinal Ganglion Cells in NMDA-Induced Neurotoxicity and a Mouse Model of Normal Tension Glaucoma

Abstract: PURPOSE. We assess if a retinal ganglion cells (aRGCs) and intrinsically photosensitive retinal ganglion cells (ipRGCs) survive in mouse models of glaucoma. METHODS. Two microliters of N-methyl-D-aspartate (NMDA; 1 mM) or PBS were injected intraocularly 7 days before sacrifice. Immunohistochemical analyses of the retina were performed using antibodies against RNA-binding protein with multiple splicing (RBPMS), osteopontin, and melanopsin. Immunohistochemical analyses also were performed in adult mice with glut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
3
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 57 publications
0
30
3
3
Order By: Relevance
“…In our study, the neuroprotective effect of ripasudil was modest considering the suppression rate of p-p38 in the retina. We previously reported that some RGC subtypes are highly tolerant to neurotoxicity and glaucoma-like www.nature.com/scientificreports/ degeneration in glaucoma model mice 22 . Subtype-specific susceptibility to RGC death is also observed after ONC 23,24 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, the neuroprotective effect of ripasudil was modest considering the suppression rate of p-p38 in the retina. We previously reported that some RGC subtypes are highly tolerant to neurotoxicity and glaucoma-like www.nature.com/scientificreports/ degeneration in glaucoma model mice 22 . Subtype-specific susceptibility to RGC death is also observed after ONC 23,24 .…”
Section: Discussionmentioning
confidence: 99%
“…Mice were perfused with Zamboni's fixative and eyes were enucleated, postfixed in Zamboni's fixative for 2 h at 4℃. Retinas were then isolated from the eyecup, incised radially into four radial pieces 22 . For immunolabeling with an RBPMS antibody, the retinas were first incubated for 2 h in a blocking solution containing 5% horse serum and 1% Triton X-100 in PBS (pH 7.4).…”
Section: Drug Administrationmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathogenesis of NMDA to induce the apoptosis of RGCs is excitotoxicity 29 . Before the animal procedures, the rats were anaesthetized with ketamine (80 mg/kg) and xylazine (12 mg/kg) (Ilium, Troy Laboratories Pty.…”
Section: Methodsmentioning
confidence: 99%
“…The cell body of RGCs is located in the retina and they project their axons to the brain nuclei through the optic nerve. To date, more than 40 subtypes of RGCs have been identified and how they respond to injury has been studied in various models [1][2][3][4]. Glaucoma therapy mainly focuses on reducing IOP and this approach prevents or slows down disease progression.…”
Section: Introductionmentioning
confidence: 99%